Dispute resolution in the construction industry an evaluation of British practice - Gould, Nicholas, 1942- (Thomas Telford, 1999)
This title works its way through the spectrum of dispute resolution techniques, negotiation, mediation and conciliation, expert determination, adjudication, arbitration, litigation and more.